Activation of angiotensin type 2 receptors prevents diabetic complications in female db/db mice by nitric oxide‐mediated mechanisms - Dominici, Fernando Pablo (2020)
Background and Purpose: The AT2 receptor plays a role in metabolism by opposing the actions triggered by the AT1 receptors. Activation of AT2 receptors has been shown to enhance insulin sensitivity in both normal and insulin resistance animal models. In this study, we investigated the mechanism by which AT2 receptors activation improves metabolism in diabetic mice. Experimental Approach: Female diabetic (db/db) and non-diabetic (db/+) mice were treated for 1 month with the selective AT2 agonist, compound 21 (C21, 0.3 mg·kg−1·day−1, s.c.). To evaluate whether the effects of C21 depend on NO production, a subgroup of mice was treated with C21 plus a sub-pressor dose of the NOS inhibitor l-NAME (0.1 mg·ml−1, drinking water). Key Results: C21-treated db/db mice displayed improved glucose and pyruvate tolerance compared with saline-treated db/db mice. Also, C21-treated db/db mice showed reduced liver weight and decreased hepatic lipid accumulation compared with saline-treated db/db mice. Insulin signalling analysis showed increased phosphorylation of the insulin receptor, Akt and FOXO1 in the livers of C21-treated db/db mice compared with saline-treated counterparts. These findings were associated with increased adiponectin levels in plasma and adipose tissue and reduced adipocyte size in inguinal fat. The beneficial effects of AT2 receptors activation were associated with increased eNOS phosphorylation and higher levels of NO metabolites and were abolished by l-NAME. Conclusion and Implications: Chronic C21 infusion exerts beneficial metabolic effects in female diabetic db/db mice, alleviating type 2 diabetes complications, through a mechanism that involves NO production.